Comparative Evaluation of Cention with Glass Ionomer Cement, Composite Resins and Silver Amalgam with Respect to Mechanical Strength: An in-Vitro Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Numerous direct filling materials are available to the modern dental practice from amalgams,GIC to modern bulk fill composites. Cention is an “alkasite” restorative. Alkasite refers to a new categoryof filling material, which like compomer or ormocer materials is essentially a subgroup of the compositematerial class. This new category utilizes an alkaline filler, capable of releasing acid-neutralizing ions. It isa tooth-colored, basic filling material for direct restorations. It is self-curing with optional additional lightcuring. It is radiopaque, and releases fluoride, calcium and hydroxide ions. As a dual-cured material it can beused as a full volume (bulk) replacement material. Hence the Aim of the study was to compare the Alkasite(Cention N) with Silver amalgam, GIC and Composite to evaluate the Compressive strength & diametraltensile strength.Materials and Method: Split molds of dimension 6 [height] x4 [diameter] was used to fabricate 15 samplesof each material for testing the compressive strength and for tensile strength. And subjected under UniversalInstron testing machine connected to a load measuring cell, to recorded load applied to the samples at acrosshead speed of 0.75 ± 0.25 mm/min till the samples fracture.Results: Composite and Cention N showed significantly higher strength than Silver Amalgam and Glassionomer cement.Conclusion: Within the limitation of this study, it can be concluded that Cention N can be used as a superioralternative when compared with Silver Amalgam and Glass ionomer cement.